2019
DOI: 10.1177/0954410019844067
|View full text |Cite
|
Sign up to set email alerts
|

Pressure gradient effects on wake-flow instabilities behind isolated roughness elements on re-entry capsules

Abstract: Laminar-turbulent transition caused by modal disturbance growth in the wake flow of isolated roughness elements on blunt re-entry capsules is studied numerically at typical cold hypersonic wind-tunnel conditions. Two fundamentally different heat shield shapes are considered. On the sphere-cone forebody the wake flow of the roughness is exposed to an adverse pressure gradient, whereas the spherical heat shield exhibits a strongly favorable pressure gradient. The pressure gradient effects on the development of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…The relatively short optimal optimization length is consistent with the findings of Theiss et al 17,18 for the laminar wake flow development behind an isolated roughness element on the forebody of the HLB capsule. The authors have shown that due to the strongly favorable pressure gradient, 44 the laminar wake flow experiences growth and decay of the streak amplitude (and also modal disturbance growth) only within a few roughness diameters downstream of the element. Although not shown here, choosing G out E as objective function, the boundary layer on both capsule forebodies undergoes optimal non-modal disturbance growth within 30-40 boundary-layer thicknesses depending on the angular coordinate, which is about fifteen times shorter in comparison to the findings of Reshotko & Tumin 11 for flat plate flows.…”
Section: A Effects Of Unit Reynolds Number and Energy Normmentioning
confidence: 99%
“…The relatively short optimal optimization length is consistent with the findings of Theiss et al 17,18 for the laminar wake flow development behind an isolated roughness element on the forebody of the HLB capsule. The authors have shown that due to the strongly favorable pressure gradient, 44 the laminar wake flow experiences growth and decay of the streak amplitude (and also modal disturbance growth) only within a few roughness diameters downstream of the element. Although not shown here, choosing G out E as objective function, the boundary layer on both capsule forebodies undergoes optimal non-modal disturbance growth within 30-40 boundary-layer thicknesses depending on the angular coordinate, which is about fifteen times shorter in comparison to the findings of Reshotko & Tumin 11 for flat plate flows.…”
Section: A Effects Of Unit Reynolds Number and Energy Normmentioning
confidence: 99%
“…The relatively short optimal optimization length is consistent with the findings of Theiss et al [17,18] for the laminar wake flow development behind an isolated roughness element on the forebody of the HLB capsule. The authors have shown that, due to the strongly favorable pressure gradient [44], the laminar wake flow experiences growth and decay of the streak amplitude (and also modal disturbance growth) only within a few roughness diameters downstream of the element. Although not shown here, choosing J out E as the objective function, the boundary layer on both capsule forebodies undergoes optimal nonmodal disturbance growth within 30-40 boundary-layer thicknesses depending on the angular coordinate, which is about 15 times shorter in comparison to the findings of Reshotko and Tumin [11] for flat plate flows.…”
mentioning
confidence: 99%